2021
DOI: 10.1002/evan.21929
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the “muddle in the middle”: The case for Homo bodoensis sp. nov.

Abstract: Recent developments in the field of palaeoanthropology necessitate the suppression of two hominin taxa and the introduction of a new species of hominins to help resolve the current nebulous state of Middle Pleistocene (Chibanian) hominin taxonomy. In particular, the poorly defined and variably understood hominin taxa Homo heidelbergensis (both sensu stricto and sensu lato) and Homo rhodesiensis need to be abandoned as they fail to reflect the full range of hominin variability in the Middle Pleistocene. Instead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 549 publications
(34 citation statements)
references
References 129 publications
(238 reference statements)
1
33
0
Order By: Relevance
“…When viewed from a macroevolutionary perspective a similar scenario, extended also to Eurasia, might describe the evolutionary history of the entire group—that is, the “pan group”—from which our species ultimately originated. In this case, it should therefore be referred to the putatively ancestral, geographically widespread and phenetically diversified (as well as taxonomically controversial 130,146 ). Homo heidelbergensis , 101 including the diverging Neanderthal and Denisovan lineages, viewed as part of the crown group to which H. sapiens belongs too.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When viewed from a macroevolutionary perspective a similar scenario, extended also to Eurasia, might describe the evolutionary history of the entire group—that is, the “pan group”—from which our species ultimately originated. In this case, it should therefore be referred to the putatively ancestral, geographically widespread and phenetically diversified (as well as taxonomically controversial 130,146 ). Homo heidelbergensis , 101 including the diverging Neanderthal and Denisovan lineages, viewed as part of the crown group to which H. sapiens belongs too.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, such a rather polymorphic record was usually referred to as "archaic Homo sapiens," while more recently it has been viewed as representing one (Homo heidelbergensis 101 ) or more species, such as Homo heidelbergensis and/or Homo rhodesiensis 129 and/or Homo helmei and/or Homo bodoensis. 88,89,130 These variable morphologies of the Middle Pleistocene provide the context to think about the basal population of anatomically modern humans, particularly in a period in which localized populations were strongly subject to both selective pressures and genetic drift.…”
Section: Extended Single-african-origin: a Renewed Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…Roksandic et al 1 surveyed Middle Pleistocene Homo (especially in Africa) and came to three questionable conclusions: they argued against the current wide usage of the species nomen heidelbergensis (type specimen the Mauer mandible); they argued against the species nomen rhodesiensis (type specimen the Kabwe 1 or Broken Hill cranium) and suggested the new name Homo bodoensis (type specimen the Bodo 1 cranium) for the same population; they suggested that the latter population/sample/species was the likely direct ancestor of Homo sapiens .…”
mentioning
confidence: 99%
“…As discussed in Roksandic et al, 1 the International Code of Zoological Nomenclature 2 is a set of legalistic (rather than biological) rules for naming and modifying names of animal taxa. One of the primary underlying regulations is priority, that is, the name first applied to a taxon holds sway except in the case of an argument that another name for the same taxon has become entrenched in common usage and application of priority would result in loss of nomenclatural stability.…”
mentioning
confidence: 99%